Influence of micro-cracking on capillary water absorption of an UHPFRC - Matos, A. M. (2018)
The aim of this research was to investigate the influence of cracking on water transport by capillary suction in UHPFRC. Specimens were firstly pre-loaded under four-point bending up to a wide range of pre-defined crack open displacement. Crack pattern created was characterized (width, number of cracks) before capillarity testing. Test results showed that micro cracks induced by previous loading significantly increased the sorptivity comparing with non-cracked specimens. However, increasing the damage (COD of 200 up to 400 ?m), did not significantly compromise the absorption capillary suction of UHPFRC, as compared to good quality conventional concrete or engineered cementitious composites (ECC).